Analysis of Phonetic Errors in Reading Arabic Texts for Junior High School Students - Jamil, Khairul; Maulidah, Nurul Hikmah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study analyzes errors in reading Arabic texts for SMPIT Ghafa Education Foundation Medan students. This research is qualitative with a case study approach. The research subjects were 50 students selected by snowball sampling technique. The research data is in the form of students' phonetic errors in reading Arabic texts of Arabic books at SMPIT Ghafa Education Foundation Medan, the factors underlying the errors, and solutions for correcting language errors. Data sources were obtained from students, teachers, and school stakeholders. Observation, interviews, and documentation carry out data collection techniques. In comparison, data analysis is done through data reduction, data presentation, and conclusion. The results showed that the form of students' Arabic language errors was characterized by errors in a pronouncing vowel and consonant sounds for several Hijaiyyah letters, such as sound construction, replication, repetition, misplaced letters, and short lengths of Arabic letters. Various forms of errors are motivated by several factors, both internal and external, both from the students themselves, teachers, schools, and families. As for these, Arabic language errors can be minimized by holding drills at each study meeting, motivating students to study hard, participating in training and workshops on learning methodologies for Arabic teachers, and increasing parents' enthusiasm in accompanying student learning. Thus, the results of errors in Arabic for SMPIT Ghafa Education Foundation Medan students can be corrected. Schools can reconstruct better Arabic learning methodologies to realize the school's mission.